Neoproterozoic reworking of the Palaeoproterozoic Capricorn Orogen of Western Australia and implications for the amalgamation of Rodinia - Occhipinti, Sandra; Reddy, Steven (Geological Society, London, 2009)
Argon isotopic data from mica from the southern Capricorn region of Western Australia record complex intra- and inter-grain systematics that reflect modification due to a range of processes. However, 40Ar/39Ar age distributions, though complex, generally show early Neoproterozoic ages in the west, increasing to Mesoproterozoic ages in the east. Palaeoproterozoic ages associated with cooling after the c.1.8 Ga Capricorn Orogen or c.1.6 Ga Mangaroon Orogen are not preserved. These data reflect cooling from a ~300C thermal overprint that took place prior to 960 Ma that is related to the enigmatic Edmunian Orogeny. These data, combined with sediment provenance data from the Early Neoproterozoic Officer Basin and U-Pb age data from the nearby Pinjarra Orogen, indicate that the late Mesoproterozoic - Neoproterozoic Pinjarra and Edmundian events are dynamically linked and reflect tectonic activity on the western margin of the amalgamated West Australian Craton. The temporal framework for this event suggest a link to the evolving Rodinian supercontinent and reflect the oblique collision of either Greater India or Kalahari cratons with the West Australian Craton. These results illustrate that the temporal evolution of poorly preserved orogens can be constrained by low-temperature thermochronology in the adjacent cratons.